2009
DOI: 10.1123/jpah.6.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Computerized 24-Hour Physical Activity Recall (24PAR) Instrument With Pattern-Recognition Activity Monitors

Abstract: The results of this study support the overall utility of the 24PAR for group-level estimates of daily EE and MVPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
4
33
1
1
Order By: Relevance
“…A unique aspect of the SenseWear Armband is that the proprietary algorithms applied by the software to estimate EE are continuously being improved by the manufacturer in an effort to reduce error. Several studies have demonstrated that the enhancements improve the accuracy of the assessment (Calabró, Welk, & Eisenmann, 2009;Calabro et al, 2009;Jakicic et al, 2004;Smith, Foster, & Campbell, 2011). Our research group has contributed to this work by collecting data needed to "train" the algorithms.…”
Section: Discussionmentioning
confidence: 98%
“…A unique aspect of the SenseWear Armband is that the proprietary algorithms applied by the software to estimate EE are continuously being improved by the manufacturer in an effort to reduce error. Several studies have demonstrated that the enhancements improve the accuracy of the assessment (Calabró, Welk, & Eisenmann, 2009;Calabro et al, 2009;Jakicic et al, 2004;Smith, Foster, & Campbell, 2011). Our research group has contributed to this work by collecting data needed to "train" the algorithms.…”
Section: Discussionmentioning
confidence: 98%
“…The estimates of group-level EE were within 100 kcal of the estimates from the Sensewear (~ 5%–6% error) and these differences were not statistically or practically significant (effect sizes of < 0.20). A unique contribution of the study (7) is that we observed no differences in validity when used with or without a behavioral log designed to remind participants of their behavior. This suggests that participants can provide a reasonably accurate recall of their previous day’s activity using this type of interviewer-administered tool.…”
Section: Introductionmentioning
confidence: 89%
“…While still prone to error, the time frame is short enough that participants are able to accurately recall duration of active and sedentary periods in a reasonably objective way (36). Previous work by our team evaluated the utility of an interviewer-administered 24-hour Physical Activity Recall (PAR) against temporally matched data from SenseWear Armband (SWA) monitors (7). We reported moderate to high correlations (r = 0.57) for reported levels of moderate to vigorous physical activity (MVPA) and high correlations (r = 0.88) for estimates of energy expenditure (EE).…”
Section: Introductionmentioning
confidence: 99%
“…The PAR protocol was based on an established, facilitated recall methodology shown in previous studies to be effective for capturing details about the type and intensity of occupational, household and leisure-time PA (6, 19). Participants are asked to provide details about the type and intensity of PA performed in the day and the raw PA data are converted into estimates of EE using established metabolic equivalent (MET) codes from the Compendium of PA (1).…”
Section: Methodsmentioning
confidence: 99%